Analisis Pengaruh Penataan Organisasi LIPI Terhadap Kinerja ASN Pendukung IPTEK Di Lingkungan LIPI - Fitrianingrum, Lia; Lusyana, Dina; Lellyana, Debby (Jurnal Administrasi dan Kebijakan Publik, 2021)
The Indonesian Institute of Sciences has carried out a comprehensive organizational restructuring (reorganization) in all lines. It has simplified the bureaucracy by minimazing organization structure, and optimizing organization functions. This reorganization was set in LIPI Regulation No.1 of 2019 concerning the Organization and Work Procedure of the Indonesian Institute of Sciences (SOTK-LIPI), which has made fundamental changes to the overall service business process at LIPI, and has affected on science and technology supporting employees. This organizational arrangement aims to create competency-based research and service governance. The reorganization policy at LIPI is the basis for redistribution of science and technology supporting employees. This has changed the mobility of supporting employees, from stagnant and limited environment to dynamic and focused on service functions according to their specializations and functional positions. This research is focused on examining the effect of organizational restructuring on the performance improvement of science and technology supporting employees of LIPI, after LIPI Regulation concerning the Organization and Work Procedure is published. The research method used is explanatory survey. The data analysis technique used to test the model is multiple linear regression. The respondents who became the unit of analysis were as many as 200 respondents of science and technology supporting employees at LIPI. The results of this study indicate that the performance of supporting employees is simultaneously influenced by organizational rearrangement which includes reorganization of structure, technology, physical settings, and people.